Effects of Music Therapy on Aphasia and Cognition of Patients with Post-stroke: A Systematic Review and Meta-analysis - Dajiao Gong; Fengfang Ye (Noise and Health)
Purpose: This investigation sought to systematically assess music therapy’s impact on aphasia and cognition in patients with post-stroke. Methods: Comprehensive searches were performed across major databases, including PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, and Vip Chinese sci-tech periodicals (VIP), covering publications up to December 2023. After screening and extracting data from the retrieved literature, its quality was appraised, which was followed by a meta-analysis using RevMan software (version 5.4, Cochrane Collaboration, Oxford, UK). Results: Nine articles, which were published from 2008 to 2022, were covered in this investigation, comprising 309 stroke patients in total. Meta-analysis results from these variations were found to be not statistically significant in the degree of functional communication improvement between the experimental group and the control group (standardized mean difference [SMD] = 0.23, 95% confidence interval [CI] (−0.19; 0.77), P > 0.05). These variations were found to be not statistically significant in the improvement of understanding ability in the experimental group compared with that in the control group (SMD = 0.21, 95% CI [−0.66; 1.09], P > 0.05). The degree of improvement in repetitive ability of the experimental group was considerably greater than that of the control group (SMD = 0.37, 95% CI [0.01; 0.76], P < 0.05). These variations were found to be not statistically significant in the improvement of naming ability in the experimental group compared with that in the control group (SMD = 0.30, 95% CI [−0.19; 0.80], P > 0.05). The cognitive score of the experimental group was considerably greater than that of the control group (SMD = 0.75, 95% CI [0.44; 1.06], P < 0.05). Conclusion: Music therapy can effectively ameliorate the repetition ability of patients with aphasia after stroke. It can also improve the cognitive ability of patients. Thus, music therapy could be further applied to treat this type of patients.